Multiobjective routing in multiservice MPLS networks with traffic splitting — A network flow approach - Girão-Silva, Rita (2015)
A multiobjective routing model for Multiprotocol Label Switching networks with multiple service types and traffic splitting is presented in this paper. The routing problem is formulated as a multiobjective mixed-integer program, where the considered objectives are the minimization of the bandwidth routing cost and the minimization of the load cost in the network links with a constraint on the maximal splitting of traffic trunks. Two different exact methods are developed for solving the formulated problem, one based on the classical constraint method and another based on a modified constraint method. A very extensive experimental study, with results on network performance measures in various reference test networks and in randomly generated networks, is also presented and its results are discussed.